2012
DOI: 10.1111/j.1365-2109.2012.03095.x
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution and sexual maturation in cage-farming of Atlantic cod (Gadus morhuaL.) exposed to natural or continuous light

Abstract: The vertical distribution and seasonal timing of sexual maturation were investigated in Atlantic cod in four large commercial sea cages in Northern Norway during their second year of on-growth. Replicate cages were exposed to either natural light (NL) or continuous light (LL) from May 2007 to January 2008. Hydro-acoustic monitoring revealed that the cod in the NL cages were mainly distributed from 5 to 13 m depth at day while they were more dispersed and swam deeper at night. A clear ascent was observed prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
0
4
0
1
Order By: Relevance
“…From salmon studies, it is known that flesh texture becomes watery and tough during sexual maturation (Aksnes, Gjerde, & Roald, 1986). It is also known that GSI is a good indicator for maturation status in cod (Skulstad et al, 2013), and failure to include this factor, together with size and sex, might contribute to misinterpretations of results. However, variations in experimental design, environmental conditions, and genetics will also make it challenging to strictly compare results among studies.…”
Section: Figmentioning
confidence: 97%
“…From salmon studies, it is known that flesh texture becomes watery and tough during sexual maturation (Aksnes, Gjerde, & Roald, 1986). It is also known that GSI is a good indicator for maturation status in cod (Skulstad et al, 2013), and failure to include this factor, together with size and sex, might contribute to misinterpretations of results. However, variations in experimental design, environmental conditions, and genetics will also make it challenging to strictly compare results among studies.…”
Section: Figmentioning
confidence: 97%
“…Due to these negative effects, researchers and farmers were exploring ways to delay or inhibit early maturation through manipulating environmental parameters (photoperiod, temperature), feeding practices (ration, frequency) and nutrition 70,72,223,225,228‐230 . These continuous light regimes are successful in controlling early maturation of farmed cod in indoor tanks 70,228,229 but similar results could not be achieved in sea cages and even strong CL treatment often only delays puberty by 4–6 months, perhaps due to the interference of strong ambient light cycle in sea cages 231 . However, Kolbeinshavn et al 232 showed that farmed cod reared under artificial light in sea cages had 33% higher weight (approx.…”
Section: Cage Productionmentioning
confidence: 99%
“…Thus, tactical use of continuous light in sea cages can offer better results in terms of growth and delaying sexual maturation. It is suggested that subsurface feeding regimes at deep in the sea cages would prevent the need to ascent to surface water (when fed on the surface) 231 and the cod would experience more consistent light regime which could minimize the effects of external ambient light on maturation. Spectral quality of the lightening system could also be an issue for the failure of arresting early maturation, and it should match the natural light spectrum 234 …”
Section: Cage Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eles são capazes de detectar alterações nos organismos que podem ocorrer tanto em níveis celulares, bioquímicos, moleculares ou fisiológicos (LAM;GRAY, 2003), devido a fatores endógenos e exógenos de diferentes fontes. Estas alterações podem comprometer o crescimento, a engorda, o desenvolvimento gonadal, a reprodução e a capacidade imunológica (PRUNET et al, 2012;NAKANO et al, 2013;SKULSTAD et al, 2013;GOOD et al, 2014;HOSEINI et al, 2015). Além de ser possível realizar testes para verificar os motivos de uma redução de crescimento dos peixes criados, os biomarcadores podem esclarecer diversos problemas na criação como, por exemplo, a tolerância dos organismos à hipoxia, a compostos nitrogenados, a contaminantes e a variações na qualidade ambiental (RODRIGUES et al, 2011;PRUNET et al, 2012;MAHFOUZ et al, 2015;KALANTZI et al, 2016), mesmo antes que a saúde do animal esteja muito comprometida ou que a mortalidade ocorra.…”
Section: Introdução Geralunclassified